2001
DOI: 10.1046/j.1365-2133.2001.04228.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG, IgA and IgE autoantibodies against the ectodomain of desmoglein 3 in active pemphigus vulgaris

Abstract: In extension of previous findings, our study demonstrates that, in addition to IgG autoantibodies, IgA and occasionally IgE autoantibodies reactive with Dsg3 are present in acute and chronic active PV. The detection of Dsg3-reactive autoantibodies of the IgG4, IgA and IgE subclasses in active PV provides additional evidence that PV is a T-helper 2-regulated autoimmune disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 29 publications
5
52
0
Order By: Relevance
“…1D, E, F). In both PV and PF, patients with active disease demonstrate DSG-reactive IgG4 and IgG1, while patients in remission and some healthy relatives of pemphigus patients can demonstrate only anti-DSG IgG1 [27,28,37,72,73]. Probably IgG2 and IgG3 anti-DSG abs have not been associated with pemphigus [7,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1D, E, F). In both PV and PF, patients with active disease demonstrate DSG-reactive IgG4 and IgG1, while patients in remission and some healthy relatives of pemphigus patients can demonstrate only anti-DSG IgG1 [27,28,37,72,73]. Probably IgG2 and IgG3 anti-DSG abs have not been associated with pemphigus [7,74].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed that autoreactive T-cells show the features of Th1, as well as Th2, in patients with PV [21][22][23], PF [24] and BP [25,26]. Thus, probably both autoreactive Th1-and Th2-cells may be involved in the regulation of the production of pathogenic abs by B-cells in pemphigus/BP and in these patients autoimmunity against DSG-/DEJ-components may be Th1-regulated for IgG1 and Th2-regulated for IgG4 [27,28]. It is suggested that DSG3-and BP180-reactive Tcells, respectively in PV and BP, presumably foster the production of abs of the Th2-dependent IgG4 subtype, that are preferentially seen in active stages of these disorders [6].…”
Section: A B C Dmentioning
confidence: 99%
“…By magnetic cell sorting (MACS) cytokine secretion assay, Dsg3-reactive Th2 cells were detected at similar frequencies in acute onset, chronic active, and remittent PV, while the number of autoreactive Th1 cells exceeded that of Th2 cells in chronic active PV (18). Autoreactive Th1 and Th2 cells may be involved in the regulation of the production of pathogenic autoantibodies by B cells in PV since sera of patients with PV contain Th1-regulated IgG1 and Th2-regulated IgG4 autoantibodies directed against Dsg3 (Figure 3) (19,20).…”
Section: Autoreactive T Lymphocytes In Pemphigusmentioning
confidence: 99%
“…[131] In the same study, IgE-anti-desmoglein 3 was detected more frequently in the sera of patients with acute onset compared to chronic active pemphigus vulgaris. [131,132] In summary, IgE reactivity seems to be more relevant in the endemic form of pemphigus foliaceus than in pemphigus vulgaris. …”
Section: Other Pemphigoid Diseasesmentioning
confidence: 99%